A challenging case of metastatic pulmonary calcification in a predialysis patient - Silva,Joana R (2017)
A 45-year old white female with personal history of psychiatric disorder, severe hypokalaemia, medullary sponge kidney and chronic kidney disease, not on dialysis, was admitted to the Emergency Department after syncope. She was hypotensive and dehydrated. Arterial blood revealed metabolic alkalosis and no hypoxaemia. Laboratory tests revealed altered renal function, hypokalaemia, hyperparathyroidism, normal calcaemia and slightly elevated phosphorus. Exuberant alterations on chest radiography led to performing a chest computed tomography, which was suggestive of pulmonary metastatic calcification. She also had signs of calcification of the kidney. The main diagnoses were chronic kidney disease, medullary sponge kidney, hypokalaemia, dehydration, hypotension and pulmonary metastatic calcification. Tissue calcification can be metastatic or dystrophic. Pulmonary metastatic calcification is most commonly due to chronic kidney disease. Risk factors for tissue calcification in this patient were chronic kidney disease, hyperparathyroidism and elevated phospho-calcium product. The hyperparathyroidism was most probably secondary. Treatment aimed at correcting the water and electrolyte disturbances and admission to the psychiatric ward, with improvement of renal function, normalization of blood pressure and correction of the hypokalemia. To treat hyperparathyroidism, she was referred for parathyroidectomy